The Dynamic Writing of Mario Bellatin: from Text to Theater and Theater to Text (2018)
Towards the end of XXth century and the beginning of the XXIst in Latin America, narrative texts are produced which respond to the search for a relationship between literature and art (both inside texts and outside them). In this relationship, the body has a fundamental role. This paper aims at analyzing Mario Bellatin ́s La escuela del dolor humano de Sechuán [The Szechuan School of Human Suffering] (2005) and Poeta ciego [Blind Poet] (2010) by considering the figure of mise-en-scène. In its displacement into literary writing, this figure is understood as the arrangement of the stage-like space where characters perform cultural, ritual and theatrical actions through a particular narrative voice. Finally, the mise-en-scène stages performatic bodies as well as a “third body”, using Esposito ́s term, which remains outside enunciation